477 Stereotactic Radiosurgery With Versus Without Prior Onyx Embolization for Brain Arteriovenous Malformations. (April 2023) - Chen, Ching-Jen; Ding, Dale; Lee, Cheng-chia; Kearns, Kathryn; Pomeraniec, Isaac Jonathan; Cifarelli, Christopher Paul; Liscak, Roman; May, Jaromir; Williams, Brian Jeremy; Ironside, Natasha; Burke, Rebecca M.; Warnick, Ronald E.; et al.
Abstract : INTRODUCTION: Investigations of the combined effects of neoadjuvant Onyx embolization and stereotactic radiosurgery (SRS) on brain arteriovenous malformations (AVM) have not accounted for initial angioarchitectural features prior to neuroendovascular intervention. METHODS: The International Radiosurgery Research Foundation AVM databases from 1987–2018 were retrospectively reviewed. Patients were categorized, based on AVM treatment approach, into Onyx embolization and SRS (OE+ SRS) or SRS alone (SRS-only) cohorts and then propensity score-matched in a 1:1 ratio. Primary outcome was AVM obliteration. Secondary outcomes were post-SRS hemorrhage, all-cause mortality, radiologic and symptomatic radiation-induced changes (RIC), and cyst formation. Comparisons were analyzed using crude rates and cumulative probabilities adjusted for competing risk of death. RESULTS: The matched OE + SRS and SRS-only cohorts each comprised 53 patients. Crude rates (37.7% vs. 47.2% for OE + SRS vs. SRS-only cohorts, respectively; OR = 0.679, p = 0.327) and cumulative probabilities at 3, 4, 5, and 6 years (33.7%, 44.1%, 57.5%, and 65.7% for OE + SRS cohort vs. 34.8%, 45.5%, 59.0%, and 67.1% for SRS-only cohort, respectively; SHR = 0.961, p = 0.896) of obliteration were similar between the matched cohorts. The secondary outcomes of the matched cohorts were also similar. Asymptomatic and symptomatic embolization-related complication rates in the matched OE + SRS cohort were 18.9% and 9.4%, respectively. CONCLUSIONS: Pre-SRS AVM embolization with Onyx does not appear to negatively influence outcomes after SRS. Our analyses, based on de novo nidal characteristics, thereby refute previous studies that found detrimental effects of Onyx embolization on SRS-induced AVM obliteration. However, given the risks incurred by nidal embolization using Onyx, this neoadjuvant intervention should be employed judiciously in multimodal treatment strategies involving SRS for appropriately selected large-volume or angioarchitecturally high-risk AVMs.